Pengaruh strategi pembelajaran dan gaya kognitif spasial terhadap hasil belajar ikatan kimia sma - Rosari, Intan (IJIS Edu : Indonesian Journal of Integrated Science Education, 2019)
Abstract: The Effect of Instructional Organizing Strategi with Spatial Cognitive Style on Learning Outcomes of Student Class Eleven science of Chemical Bond. This thesis aims to determine the effect the different micro strategis on organizing instruction to improve students learning outcomes in Chemical Bond. A 2x2 factorial design is used for this experiment conducted at the Global Islamic Senior High school and PB Sudirman Senior High School in Jakarta. A sample of 56 student was taken using multi stage sampling. Based on their spatial cognitive style the sample is then divided into two groups, high and low spatial cognitive style.The instruments were use for this research are two kinds, is it (1) Test for predict Chemistry learning Outcomes; (2) Instrumen for predict Spatial Cognitive Style. For Analysis Test include Normality Test with Liliefors Test and Homogenity with Bartlett Test; for Hypotesist test we use Varians analysis two path (2x2)In order to avoid contamination of treatment, the defferent micro strategis are implemented differently in the each school. The result of this research are as follows: (1) In general, to improve learning outcome in Chemical Bond, it is better to use the Merrill model micro strategi on organizing the Component Display Theory (CDT) than to use the Taba Model Strategy on organizing instruction the Concept Formation; (2) Spatial Cognitive style of the student affect student learning outcomes in Chemical Bond. Student who have high spatial cognitive style get better learning outcomes in Chemical Bond the student who have low spatial cognitive style; (3) There is an interaction between micro strategy on organizing instrustion with student spatial cognitive style, Merrill Model Strategy on organizing instruction instruction using Component Display Theory (CDT) implementation is more effective in increasing student learning outcome in Chemical Bond than Taba model strategy on organizing instruction Concept Formation; For student with high spatial cognitive style, both strategies can be implemented because there are no differences obtained in student learning outcomes in Chemical Bond using both of the organizing strategies.Keyword: Instructional Organizing Strategy, Spatial Cognitive Style, Chemical Bond, Learning Outcomes Abstrak: Pengaruh Strategi Pembelajaran Dan Gaya Kognitif Spasial Terhadap Hasil Belajar Ikatan KimiaTesis ini bertujuan untuk menentukan pengaruh variabel-variabel bebas yaitu strategi pengorganisasian isi pembelajaran dan gaya kognitif spasial terhadap hasil belajar siswa sebagai variabel terikat pada pokok bahasan Ikatan Kimia. Penelitian ini dilaksanakan di SMA Global Islamic School Jakarta dan SMA PB Sudirman Jakarta. Dengan total sampel yang diambil adalah 56 orang siswa untuk menentukan gaya kognitif spasial kemudian dibagi menjadi gaya kognitif spasial tinggi dan gaya kognitif spasial rendah.Instrumen yang digunakan dua macam yaitu (1) tes pengukur hasil belajar Ikatan Kimia; (2) instrumen pengukur gaya kognitif spasial. Dalam uji persayaratan analisis meliputi Uji Normalitas dengan Uji Liliefors dan Homogenitas dengan Uji Bartlett;untuk uji hipotesis digunakan analisis varians dua jalur (2x2).Secara keseluruhan untuk meningkatkan hasil belajar Ikatan Kimia siswa, lebih baik digunakan Strategi Pengorganisasian Pembelajaran Model Component Display Theory Merrill dibandingkan dengan Strategi Pengorganisasian Pembelajaran Model Pembentukan Konsep; (1) gaya kognitif spasial merupakan salah satu karakteristik siswa yang berpengaruh terhadap tingkat pencapaian hasil belajar Ikatan Kimia; (2)Siswa yang memiliki Gaya Kognitif Spasial Tinggi memberikan hasil belajar Ikatan Kimia yang lebih baik dibandingkan dengan siswa yang memiliki Gay Kognitif Spasial Rendah;(3)terdapat interaksi antara strategi pembelajaran dengan gaya kognitif spasial siswa. Bagi siswa yang memiliki Gaya Kognitif Spasial Rendah, penerapan Strategi Pembelajaran CDT Merrill lebih efektif dalam meningkatkan hasil belajar Ikatan Kimia, dibandingkan dengan Strategi Pembelajaran PK Taba; (4) bagi siswa yang memiliki Gaya Kognitif Spasial Tinggi, kedua strategi pembelajaran dapat diterapkan, karena memberikan hasil belajar yang sama baiknya.